Desain Model Bisnis Wakaf Produktif Berbasis Komoditas Pertanian Lokal di Sumatera Utara - Muhammad Zuardi; Irma Suryani Lubis; Indri Dithisari; Lia Hartika (Lembaga Pengembangan Kinerja Dosen, 2026)
Productive waqf is an Islamic social finance instrument with significant potential to support sustainable economic development for the community. However, the management of waqf in Indonesia is still dominated by a consumptive approach, resulting in suboptimal economic impacts on the real sector and community empowerment. One strategic sector relevant to the development of productive waqf is the local agricultural sector, particularly in North Sumatra, which has potential land and superior commodities. Integrating waqf with the agricultural sector is expected to create added economic value, improve farmers' welfare, and strengthen regional food security. This study aims to design a business model for productive waqf based on local agricultural commodities using the Business Model Canvas approach. The research method employed is applied qualitative research with a case study on Lumbung Wakaf Sumatera Utara. Data collection was carried out through field observation, in-depth interviews, documentation, and Focus Group Discussions. The results of the study indicate that the management of agricultural waqf still faces limitations in the managerial capacity of nazhir and access to capital.